E COLI ENTERITIS IN VARNA DISTRICT FOR THE PERIOD 2013-2019 - Monov , D.; Kolarova - Dimitrova , M. (EurasianUnionScientists, 2021)
E coli enteritis is an acute intestinal infectious disease caused by pathogenic species of Eshcerihia coli and occurring with diarrhea, marked intoxication and disturbances in the water-electrolyte balance of the body. Aim and tasks: To study the incidence of E coli enteriditis in Varna district and the country for 2013-2019 and to analyze the main socio-demographic indicators indicators: sex, seasonality, age, etiological structure, place of work, settlement, etc.. Materials: analyzes, reports, bulletins, microbiological tests of RHI Varna and NCIPD Bulgaria, publications, visual materials. Methods: epidemiological analysis, statistical, documentary, graphical presentation of the results. Results: We consider the registered infections in Varna district for a period of 7 years and analyze the main epidemiological indicators for patients (age, sex, place of work, place of work, hospitalization) on the one hand and the contact persons found in epidemic outbreaks and preventive prophylaxis of the population. their etiological characteristics. Conclusions: 1. The incidence of E coli enteriditis in Varna district for 2013-2019. is 2 to 4 times above the national average. 2. The diseases occur throughout the year with a peak in August, mainly in cities (95.81%) among women (56.09%). 3. Leading is the group of sick children cared for at home (53.95%), followed by attending kindergartens (20.86%) and schools (9.11%). 4. Leading in the etiological characteristic are the cases determined up to the second and third group, respectively E. coli 0 78, E. coli 055, E. coli 0125, E. coli 086 and others.